The incentive behind the adaptation process of high-technology product: an empirical research. (9th May 2007) - Hamann, Danilo; Omar, Maktoba
This study investigates consumer's perception of high-technology and the drivers involved in the adaptation process. The underlying research analysed and evaluated people's buying behaviour regarding high-technology, through the literature and primary research in order to identify consumer's perception and attitudes towards high-technology products. The main areas of influence 'Price', 'Usage', 'Quality' and 'Culture' were identified and used as measurements for the primary research. Findings showed a significant impact of the reason for 'using' high-technology as well as the 'cultural' aspect on its adaptation process. The assumption of 'Price' or 'Usage' having a direct impact was found not to be valid.